Assessing the potential for a levy-based system to replace revenue from trophy hunting in South Africa - T.P. Moorhouse; A. Elwin; H. Ntuli; N.C. D’Cruze (Global Ecology and Conservation, 2023)
Trophy hunting is a contentious practice often associated by the public with charismatic African megafauna, especially lions (Panthera leo). Public pressure could potentially end trophy hunting in the near future, which many stakeholders argue could lead to negative impacts, including on species conservation and on the livelihoods of communities that depend upon it as a source of income. We investigated the potential for replacing revenue currently generated by trophy hunting in South Africa with levies - a “lion protection fee” - on international travellers to that country. Our approach recognised tourism as a source of funds for conservation action, and the influence of lions as a charismatic, flagship species. We surveyed 907 respondents who had previously visited South Africa, or would consider visiting in the future. We used van Westendorp and Gabor-Granger direct pricing methodologies to assess whether the willingness of potential visitors to pay for wildlife protection could be sufficient to compensate for any loss were trophy hunting to be banned. Our findings indicated substantial support for the proposition of being charged a “lion protection fee”: 84.2% of respondents stated that it was a “great” or a “good” idea. A minority (7.5%) had a negative view but only two of these respondents (0.2%) indicated a pro-trophy hunting attitude. Willingness-to-pay was sufficient that, under predicted 2023 numbers of tourists, daily fees could be set at a price acceptable to both overseas ($6–7 USD) and southern African tourists ($3–4 USD), and generate funds at least equalling, but potentially exceeding, those currently generated by trophy hunting ($176.1 million US per annum). We conclude that, in principal, revenue from trophy hunting in South Africa could be fully replaced by a subsidy to stakeholders as a payment for conservation action, funded by a modest levy on international tourist visitors.